2000
DOI: 10.1038/35046611
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Binding to the transferrin receptor is required for endocytosis of HFE and regulation of iron homeostasis

Abstract: HFE, the protein that is mutated in hereditary haemochromatosis, binds to the transferrin receptor (TfR). Here we show that wild-type HFE and TfR localize in endosomes and at the basolateral membrane of a polarized duodenal epithelial cell line, whereas the primary haemochromatosis HFE mutant, and another mutant with impaired TfR-binding ability accumulate in the ER/Golgi and at the basolateral membrane, respectively. Levels of the iron-storage protein ferritin are greatly reduced and those of TfR are slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
43
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 29 publications
5
43
1
Order By: Relevance
“…The high-affinity binding of HFE with TfR1 suggested that HFE-TfR1 complex formation might be important for the function of HFE protein in iron homeostasis (18)(19)(20)(21)(22)(23)(24)(25)(26). This hypothesis was supported by the observation that the transport of HFE to endosomes and the regulation of intracellular iron absorption in some cell lines depend on its association with TfR1 (27).…”
supporting
confidence: 72%
See 2 more Smart Citations
“…The high-affinity binding of HFE with TfR1 suggested that HFE-TfR1 complex formation might be important for the function of HFE protein in iron homeostasis (18)(19)(20)(21)(22)(23)(24)(25)(26). This hypothesis was supported by the observation that the transport of HFE to endosomes and the regulation of intracellular iron absorption in some cell lines depend on its association with TfR1 (27).…”
supporting
confidence: 72%
“…The high-affinity binding of HFE with TfR1 suggested that HFE-TfR1 complex formation might be important for the function of HFE protein in iron homeostasis (18)(19)(20)(21)(22)(23)(24)(25)(26). This hypothesis was supported by the observation that the transport of HFE to endosomes and the regulation of intracellular iron absorption in some cell lines depend on its association with TfR1 (27).Several studies on the interaction of HFE with TfR1 in transfected cell lines have attempted to characterize the biological effect of this interaction on iron homeostasis (22,23,(27)(28)(29)(30)(31). Several groups have reported that HeLa cells overexpressing HFE protein showed a decrease in ferritin level, an increase in TfR1, and an increase in iron regulatory protein activity, indicating lower levels of iron stores in the cells (22,23,30).…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Wild-type HFE is associated closely with ␤ 2 M, and TfR1 and is expressed on the cell surface and in the TfR1-containing endosomes (29)(30)(31)(32)(33). A number of experiments have been undertaken in which wild-type HFE was overexpressed in cultured cells and the overexpressed wild-type HFE decreased transferrin-bound iron uptake (32)(33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…By using physiological systems and heterologous expression systems, several groups have begun to characterize the role of HFE in cellular iron uptake (2)(3)(4)(5)(6)(7)(8)(9), with the latest contribution by Schwake et al, the current article in focus (Ref. 10, see p. C973 in this issue).…”
mentioning
confidence: 99%